Micromachined W-band dual-band quasi-elliptic waveguide filter. (September 2021) - Duan, Jun-ping; Shen, Xin-xin; Xiao, Hong; Zhang, Bin-zhen; Bai, Qiong
Abstract: This paper presents a W-band dual-band waveguide filter using SU-8 photoresist UV lithography technology. The filter has a parallel structure with both the bands of fourth-order quasi-elliptic responses by adopting easily manufactured coupling structures, enabling improved stopband rejection. The filter was designed to have two passbands centered at 80 GHz and 100 GHz and each band can be optimized independently without impact on the other. The fabricated prototype has small dimension errors and low surface roughness. Measured results show a good agreement with the simulated ones, with insertion losses for two passbands of 0.79 dB and 0.54 dB, return losses better than 10 dB, and fractional bandwidths of 7.2 % and 5.4 %. The experimental results are discussed and compared with the ones of similar structures using other machining techniques, confirming the feasibility of the design and fabrication methods of the filter. Highlights: The advantage of this parallel structure is that each single-band filter can be designed independently. The fabrication of the W-band filter is realized using SU-8 photoresist UV lithography technology. The fabricated prototype has good filter performance, and it is suitable for reception W-band communication applications.